Electrical and Optical Investigations on Polymer-Metal Oxide Composite Thin Films prepared by Langmuir Blodgett Technique - Bhullar, Gurpreet Kaur (My University, 2016)
We have prepared polymer and its nano-composite systems with metal oxides by chemical route and then prepared their homogenous LB films. Interaction between nanoparticles and host polymer matrix resulted in phase changes of monolayer. Orientation and ordering of polymer at air-water interface have been significantly improved by adding nanoparticles into it. These materials are characterized for electrical, optical, structural, thermal and morphological properties.It has improved many physical properties of polymer matrix like morphology, electrical and optical properties. Local Current-voltage (I-V) spectroscopy results by C-AFM show semiconducting behaviour of PANi and its nano-composite LB films and conductive data images show almost uniform current distribution through the films. These LB films have opened up opportunities for understanding of many properties for application point of view.
PHD, SPMS
Keywords: Atomic Force Microscopy; Langmuir-Blodgett Films; Polymer; Nano-composite